Любовь и смерть всегда вдвоем: Роман / Н. В. Андреева - Андреева Наталья Вячеславовна (Любовь. ru, 2002)
Экземпляры: (20180425) / Инвентарный номер: 38579 / Цена: 39.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 65 / ББК: 84(2Рос=Рус)6